Development and Optimization of Self-nanoemulsifying Drug Delivery System of Ibrutinib - Prasad, Dasari (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: The present research demonstrates the formulation of novel self-nanoemulsifying drug delivery system (SNEDDS) for potential delivery of ibrutinib by oral route. Materials and Methods: Ibrutinib SNEDDS formulation optimized using three-factor, three-level Box–Behnken design and the responses of dependent and independent variables fitted to the second-order quadratic equations and statistical validation calculated by analysis of variance. Various response surface graphs and contour plots were constructed to understand the effects of different factor level combinations on the responses. All optimized SNEDDS formulations were characterized for particle size, zeta potential (ZP), refractive index, % transmission, % drug content, Fourier transform infrared, transmission electron microscopy, and drug release study. Results: The formulations prepared using Capryol 90, Cremophor RH40, and Transcutol P (40%) indicated close comparison of the predicted values and experimental values whose droplet size, polydispersity index (PDI), and cumulative drug release varied between 157.07–236.62 nm, 0.206–0.312, and 54.28–83.78%, respectively. Based on the physicochemical parameters and in vitro dissolution studies, F2 is identified as optimized formulation with droplet size of 167.9 nm, PDI of 0.228 and −21.2 ± 1.62 mV ZP, maximum % transmission, and 100% drug loading with 85% drug released at end time of 30 min. Conclusion: A conclusion can thus be drawn from the present study stating the requirement for potential of ibrutinib delivery as SNEDDS in the effective management of lymphocytic leukemia. Stability test for a period of 3 months revealed the formulation to be stable for the specified time.